Development of a Rapid and Reliable Single-Tube Multiplex Real-Time PCR Method for HLA-A24:02 Genotyping - Wang, Yanxia; Zhang, Tingting; Zhang, Lirong; Pei, Yanrui; Zhao, Lili; Li, Yanwei; Liu, Lin; Wang, Huijuan (Pharmacogenomics, 2019)
is significantly associated with cutaneous adverse drug reactions caused by aromatic antiepileptic drugs. Here, we aimed to establish a fast and reliable detection method for genotyping. A single-tube multiplex quantitative real-time polymerase chain reaction (qPCR) assay for genotyping was established by combining allele-specific primers with TaqMan probes. A 100% concordance was observed between qPCR and SBT result in 106 Han subjects. The detection limit of the new method was 0.05 ng DNA. The positive rate of in Tibetans (55.6%, n = 81) was significantly higher than those in Han (34%, n = 106), Uighur (27.5%, n = 102), Bouyei (25.9%, n = 116) and Miao populations (26.5%, n = 113). The newly established qPCR assay was reliable for screening in clinical applications.